2018
DOI: 10.1002/wrna.1489
|View full text |Cite
|
Sign up to set email alerts
|

RNA methylation in nuclear pre‐mRNA processing

Abstract: Eukaryotic RNA can carry more than 100 different types of chemical modifications. Early studies have been focused on modifications of highly abundant RNA, such as ribosomal RNA and transfer RNA, but recent technical advances have made it possible to also study messenger RNA (mRNA). Subsequently, mRNA modifications, namely methylation, have emerged as key players in eukaryotic gene expression regulation. The most abundant and widely studied internal mRNA modification is N6‐methyladenosine (m6A), but the list of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 141 publications
(351 reference statements)
0
31
0
Order By: Relevance
“…GSK-3 also phosphorylates and destabilizes the RNA demethylase FTO (fat mass and obesity-associated protein); inhibition of GSK-3 causes accumulation of FTO which reduces overall levels of methylated (N 6 -methyladenosine or m 6 A) mRNAs (Faulds et al, 2018). In turn, m 6 A may regulate mRNA splicing, export, stability, or translation (Covelo-Molares, Bartosovic, & Vanacova, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…GSK-3 also phosphorylates and destabilizes the RNA demethylase FTO (fat mass and obesity-associated protein); inhibition of GSK-3 causes accumulation of FTO which reduces overall levels of methylated (N 6 -methyladenosine or m 6 A) mRNAs (Faulds et al, 2018). In turn, m 6 A may regulate mRNA splicing, export, stability, or translation (Covelo-Molares, Bartosovic, & Vanacova, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other than the above discussed 5′ capping and 3′ polyadenylation, recent studies have revealed a pervasive level of post-transcriptional modification in the mRNA transcriptome. In fact, more than 100 chemical moieties have been identified on the RNA molecules, and this undoubtedly contributes to an explosive increase in transcriptome complexity ( 43 , 63 , 161 , 170 , 182 , 200 ). This generally describes the area of research that aims to elucidate the role that transcriptional modifications play in transcript fate, and is now referred to as the field of epi-transcriptomics.…”
Section: Mrna Post-transcriptional Modificationsmentioning
confidence: 99%
“…In general, m6A modification promotes mRNA translation and stability. Modification of these sites can influence many steps of mRNA metabolism, including CAP-independent translation, nuclear retention, alternative splicing, P-body targeting, translational modulation, and mRNA degradation ( FIGURE 7 ) ( 2 , 10 , 25 , 29 , 43 , 57 , 63 , 158 , 161 , 170 , 182 , 200 ). Despite a broad impact on mRNA metabolism, many of the molecular details involving m6A-dependent regulation of RNA remain unknown ( 29 ).…”
Section: Mrna Post-transcriptional Modificationsmentioning
confidence: 99%
“…The objective of this review is to explore epigenetic modifications particularly relevant to RNA biology with a particular focus on those crucial in cardiovascular physiology and pathophysiology. For a general description of the regulation and effects of epigenetic changes occurring at the RNA level, the reader is redirected to recent articles that are more detailed in mechanistic terms [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%